Human Cytomegalovirus Infection Changes the Pattern of Surface Markers of Small Extracellular Vesicles Isolated From First Trimester Placental Long-Term Histocultures - Bergamelli, Mathilde; Martin, Hélène; Bénard, Mélinda; Ausseil, Jérôme; Mansuy, Jean-Michel; Hurbain, Ilse; Mouysset, Maïlys; Groussolles, Marion; Cartron, Géraldine; Tanguy le Gac, Yann; Moinard, Nathalie; Suberbielle, Elsa; et al. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are increasingly been recognized as key players in a wide variety of physiological and pathological contexts, including during pregnancy. Notably, EVs appear both as possible biomarkers and as mediators involved in the communication of the placenta with the maternal and fetal sides. A better understanding of the physiological and pathological roles of EVs strongly depends on the development of adequate and reliable study models, in particular during early pregnancy. In this study, we describe the isolation of small EVs from a histoculture model of first trimester placental explants in normal conditions or upon infection by human cytomegalovirus. Using bead-based multiplex cytometry and electron microscopy combined with biochemical approaches, we characterized these small EVs and defined their associated markers and ultrastructure. We observed that infection led to changes in the expression level of several surface markers, without affecting the secretion and integrity of small EVs. Our findings open the prospect for studying the functional role of EVs early during early pregnancy, along with the identification of new predictive biomarkers for the severity and outcome of this congenital infection, which are still sorely lacking.